Marine governance to avoid tipping points: Can we adapt the adaptability envelope?. (March 2016) - Serrao-Neumann, Silvia; Davidson, Julie L.; Baldwin, Claudia L.; Dedekorkut-Howes, Aysin; Ellison, Joanna C.; Holbrook, Neil J.; Howes, Michael; Jacobson, Christine; Morgan, Edward A.
Abstract: Combined pressures from climate change, resources demand and environmental degradation could lead to the collapse of marine systems and increase the vulnerability of populations dependent on them. In this paper an adaptability envelope framework is applied to investigate how governance arrangements may be addressing changing conditions of marine social-ecological systems, particularly where thresholds might have been crossed. The analysis focuses on three Australian case studies that have been significantly impacted by variations or changes in weather and climate over the past decade. Findings indicate that, in some cases, global scale drivers are triggering tipping points, which challenge the potential success of existing governance arrangements at the local scale. Governance interventions to address tipping points have been predominantly reactive, despite existing scientific evidence indicating that thresholds are approaching and/or being crossed. It is argued that marine governance arrangements need to be framed so that they also anticipate increasing marine social-ecological system vulnerability, and therefore build appropriate adaptive capacity to buffer against potential tipping points. Highlights: The concept of adaptability envelope is explained. Addressing tipping points requires transformative and adaptive governance system. Adaptive governance can help to increase the adaptability envelope. Anticipation of tipping points requires understanding of worst case scenario. The adaptability envelope can be used to communicate climate-related change.